Fault Recovery of Distribution Network Based on Genetic Algorithm - Tian Zeng; Wu Zhigang; Hu Weiyuan; Zhu Xudong; Jidong Shi; Wang Dongju (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Fault recovery of distribution network is realized by operating switches to change topological structure of the network. The final destination of fault recovery is power loss minimization, fault isolation and power load transfer. This article has built the mathematical model of fault recovery considering constraints of node voltage, line capacity and power flow balance. The objective function is power loss reduction. Further, the genetic algorithm is used to solve the proposed model. The optimal network structure and recovered power load could be derived through calculation. Finally, the author complied the program with Matlab and tested it on the IEEE33 bus system. The simulation and analysis results have verified the effectiveness of the proposed method. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4567